DETERMINATION OF BLACK FLY SPECIES IN TEHRAN AREA BY REARING THESE AQUATIC STAGES IN THE LABORATORY - A. Ardalan; P. Sandjan (Tehran University of Medical Sciences, 1979)
The identification of different species of Simuliidae, also called "black fly", is based on particular structure of oral and terminal appendages of their larvae add also on the special morphology of adults and pupaes. Because of their considerable flight range, the problem of finding their resting places, and also the difficulties of collecting the adult flies, breeding of this insect, in the laboratory, is particularly important for species identification in each area for this purpose, eggs larvae and pupae were obtained in some rivers and streams around Tehran and were transported to the laboratory. By producing air movement with a pump passing through the glass bottle containing the eggs. Larvae and pupae brought from the rivet and kept in the same river water with its content, we were able to produce large number of adult black flies and so, we determined species of black flies in different streams and rivers the list of which is given in the paper.